2021
DOI: 10.1155/2021/4760455
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Corm of Ensete ventricosum (Welw.) Cheesman Extract against Isoniazid and Rifampicin Induced Hepatotoxicity in Swiss Albino Mice

Abstract: Drug-induced liver injury (DILI) is one of the cumbersome health-related problems which render approximately 50% of liver failure and patients to receiving liver transplantation every year. Antituberculosis drugs such as isoniazid and rifampicin are potentially rendering hepatotoxicity. Ensete ventricosum (Welw.) Cheesman is an herbaceous perennial plant that contributes to the indigenous ethnomedicinal values for the society. This study aimed to investigate the hepatoprotective effect of corm of Ensete ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this study serum bilirubin levels in drug only induced mice showed a significant (P < 0.01) increase as compared with a normal control group of mice. This study result is in agreement with the data of other authors showing that RIF produced competition for the elimination of bilirubin by the liver [ 49 ] and a combination of INH and RIF resulted in a higher rate of inhibition hepatic clearance of bile, an increase in lipid peroxidation in the hepatocyte, and cytochrome P450 involved in the synergistic effect of RIF and INH [ 30 , 50 , 51 ]. Whereas O. integrifolia leaves extract induced mice challenged with INH and RIF (G IV) did not show a significant difference as compared with the normal control group.…”
Section: Discussionsupporting
confidence: 93%
“…In this study serum bilirubin levels in drug only induced mice showed a significant (P < 0.01) increase as compared with a normal control group of mice. This study result is in agreement with the data of other authors showing that RIF produced competition for the elimination of bilirubin by the liver [ 49 ] and a combination of INH and RIF resulted in a higher rate of inhibition hepatic clearance of bile, an increase in lipid peroxidation in the hepatocyte, and cytochrome P450 involved in the synergistic effect of RIF and INH [ 30 , 50 , 51 ]. Whereas O. integrifolia leaves extract induced mice challenged with INH and RIF (G IV) did not show a significant difference as compared with the normal control group.…”
Section: Discussionsupporting
confidence: 93%
“…On the 15 th day, the mice were fasted overnight and anesthetized with 100 mg/kg ketamine and 12.5 mg/kg xylazine injections. The mice were euthanized by cervical dislocation after 2–2.5 mL of blood collection through cardiac puncture [ 33 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The obtained serum was stored at −80°C until used for the biochemical assay. Serums were analyzed according to the standard principles and procedures outlined in the kit manufacturer's manual (SD Biosensor, Inc., Korea) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, other studies conducted on the nephroprotective effects of Ficus religiosa [7], Petroslinum crispums [41], and Turmeric [14] have been consistent with the present finding. is may happen due to cells' protective activities of phytochemicals that are found in EVCE [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cheesman is exploited for treating kidney stones, dysuria, liver diseases, expulsion of the placenta, cough, dysentery, healing of bone fractures, diabetes, and microbial infections. It also serves as a staple and costaple food [21][22][23][24]. Several bioactive constituents and minerals in the extract of corm of the Ensete genus have cell-protective effect and enhance the antioxidant defense system (AODS) of cells by scavenging free radicals [20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%